The end of diversity in art historical writing North Atlantic art history and its alternatives - Elkins, James 1955- (De Gruyter, 2021)
The End of Diversity in Art Historical Writing is the most globally informed book on world art history, drawing on research in 76 countries. In addition some chapters have been crowd sourced: posted on the internet for comments, which have been incorporated into the text. It covers the principal accounts of Eurocentrism, center and margins, circulations and atlases of art, decolonial theory, incommensurate cultures, the origins and dissemination of the "October" model, problems of access to resources, models of multiple modernisms, and the emergence of English as the de facto lingua franca of art writing